Canada and the new international economy - English, H. Edward (Harry Edward), 1924- (Published in co-operation with Carleton University by University of Toronto Press, 1961)
The authors of these essay are asking if a 'status quo' approach to commerce is desirable or possible at a time when other nations are endeavouring to strengthen their economies by new adventures in liberal trade, especially in the form of regional trade groups.